2023
DOI: 10.1002/hsr2.1495
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of body dysmorphic disorder in rhinoplasty candidates: A systematic review and meta‐analysis

Sara S. Nabavizadeh,
Reyhaneh Naseri,
Erfan Sadeghi
et al.

Abstract: BackgroundBody dysmorphic disorder (BDD) is a prevalent mental disorder, particularly in those seeking plastic surgery, leading to unnecessary surgeries and postsurgical dissatisfaction. Among the plastic surgeries, rhinoplasty is the most commonly sought, yet the data on prevalence of BDD among the candidates of rhinoplasty is limited. Therefore, this systematic review and meta‐analysis aimed to estimate the prevalence of BDD in rhinoplasty candidates.MethodsThe online libraries of Web of Science, PubMed, Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Patients with psychopathology ranging from personality disorders, including narcissistic personality disorder (NPD), to posttraumatic stress conditions, to obsessive-compulsive type disorders, such as body dysmorphic disorder (BDD), have been shown to potentially have a lower rate of satisfaction after surgery [11,27,28] . According to a study by Constantian and Lin, a history of psychological trauma including abuse or neglect was the most significant factor influencing patient satisfaction and a number of operations, and the most prominent factor driving surgery in patients with milder deformities [29] . In fact, some authors have suggested that potentially causative links exist between trauma (abuse/neglect), body image disorders, and obsessive plastic surgery [29] .…”
Section: Patient Psychosocial and Psychiatric Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with psychopathology ranging from personality disorders, including narcissistic personality disorder (NPD), to posttraumatic stress conditions, to obsessive-compulsive type disorders, such as body dysmorphic disorder (BDD), have been shown to potentially have a lower rate of satisfaction after surgery [11,27,28] . According to a study by Constantian and Lin, a history of psychological trauma including abuse or neglect was the most significant factor influencing patient satisfaction and a number of operations, and the most prominent factor driving surgery in patients with milder deformities [29] . In fact, some authors have suggested that potentially causative links exist between trauma (abuse/neglect), body image disorders, and obsessive plastic surgery [29] .…”
Section: Patient Psychosocial and Psychiatric Factorsmentioning
confidence: 99%
“…According to a study by Constantian and Lin, a history of psychological trauma including abuse or neglect was the most significant factor influencing patient satisfaction and a number of operations, and the most prominent factor driving surgery in patients with milder deformities [29] . In fact, some authors have suggested that potentially causative links exist between trauma (abuse/neglect), body image disorders, and obsessive plastic surgery [29] . Body dysmorphic disorder may be a model of the disordered adaptation to abuse or neglect, a variant of posttraumatic stress disorder.…”
Section: Patient Psychosocial and Psychiatric Factorsmentioning
confidence: 99%
“…One of the frequent complications, otitis media with effusion (OME), stands as the leading cause of conductive hearing loss in children with clefts. It tends to be both more prevalent and persistent compared with the general population 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…It tends to be both more prevalent and persistent compared with the general population. [4][5][6][7] OME originates from the dysfunction of the eustachian tube, involving changes in para-tubal muscle architecture, tubal cartilage density, tubal curvature, and luminal diameter. These alterations facilitate inadequate ventilation and negative pressure within the middle ear cavity, culminating in OME and subsequent hearing loss.…”
mentioning
confidence: 99%